1988
DOI: 10.1111/j.1540-8159.1988.tb06363.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Pacing and Valvular Surgery

Abstract: Over a 17-year period (1970-1987) 75 patients, 3% of overall valvular surgery (VS) patients have been permanently paced at the time of VS (group 1), nine have been paced long after (group 2), 12 were already paced at the time of valve replacement (group 3), and 81 had a permanent pacing lead inserted during VS without further need for permanent pacing (group 4). Based on pre-, per- and post-operative clinical and electrocardiographic data we studied these four groups (GR). Aortic disease and especially calcifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…comorbidities and age was observed [6,7]. Moreover, there has been no focus on type of surgery, namely single-valve or multi-valve surgery [8][9][10][11][12][13][14][15][16][17].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…comorbidities and age was observed [6,7]. Moreover, there has been no focus on type of surgery, namely single-valve or multi-valve surgery [8][9][10][11][12][13][14][15][16][17].…”
Section: Methodsmentioning
confidence: 99%
“…These latter studies reported the highest PM implantation incidence but have some limitations: there was no evaluation of preoperative electrocardiographic data, and considerable variability in terms of comorbidities and age was observed [6,7]. Moreover, there has been no focus on type of surgery, namely single-valve or multi-valve surgery [8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…stimulation channels (right ventricle apex via tricuspid valve) are not commonly used because of the high risk of inducing a prosthetic valve blockage and/or the premature rupture of the stimulating lead. [1][2][3] The most practical solution remains right ventricle stimulation with an epicardial lead positioned directly on the right ventricle.…”
Section: Case Reportmentioning
confidence: 99%
“…In patients with tricuspid mechanical valve prosthesis, a definitive pacemaker is usually implanted using an epicardial lead or during valve replacement intervention. [1][2][3] However, new leads specifically designed to stimulate the left ventricle via the coronary sinus recently have been introduced to the market. 4 We report the case of a 63-year-old patient affected by mitro-aortic valvulopathy with massive tricuspid regurgitation who had undergone a triple valve replacement with mechanical prosthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The routine "prophylactic" placement of epimyocardial electrodes at the time of valve surgery has been suggested as a solution, with the option of connecting these electrodes to a pulse generator under local anesthesia at a later date. 2 This, however, does not overcome the problem of a high incidence of chronic complications from such leads, like high pacing thresholds and conductor fractures. Epimyocardial leads for permanent ventricular pacing are not always necessary following tricuspid valve replacement.…”
Section: Tricuspid Valve Replacementmentioning
confidence: 99%